Produktivitas dan Faktor yang Mempengaruhi Usahatani Padi Lokal pada Lahan Tadah Hujan di Desa Tumih Kecamatan Wanaraya Kabupaten Barito Kuala Propinsi Kalimantan Selatan - Hastirullah Fitrah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2012)
This study aims to determine the technical implementation of Rainfed Rice Farming in the village of Tumih Wanaraya, to determine the costs, revenues and profits in the rainfed of rice farming the village of Tumih Wanaraya, to know Factors Affecting the Production of rainfed rice farms in the village of District Tumih Wanaraya. In This research used the survey method and observation technique. sampling using simple random sampling technique. In this research consisted  of 300 populations.  From each of these respondent farmer to be sampled 10%, the sample total of 30 people.The result of the study, indicated that Production obtained from  30 farmers respondents rice farming, amounting to 190.00 tonnes with productivity of 2.91 tonnes / ha. profit of local rice farming in the rainfed,  Tumih village during the production process is Rp 231,699,665.00  with - average of Rp 7,723,322.17 / farmers. Simultaneously  production factors the rice local  of rainfed land, the value of F-hit. 0,01 (97.74764)> F-table 0:01 (2.142), whole  of independent variables affecting on dependent variable. Partially influence of land area (X1) showed highly significant effect on the resulting production at 99% confidence level, it is seen from the value of t-hit (3.4479627)> t-tab 12:01 (2,457). Kapur (X2), based on the results of the regression analysis, these factors greatly influence the production on the 99% confidence level, for the value of t-hit (3.1487626)> t-tab value of 0:01 (2,457). Fertilizer (X3) this factor showed significant effect on the level of confidence (95%), the production due to the results of the analysis indicate that the value of t-hit (1.2520643)> t-table 0.05 (1.697). Manpower (X4), this factor indicates the effect is not significant to the production level of 95% as the value of t-hit (0.8054875) <t-table 0:05 (1,697).